Navigating Modern Retail Competition: Adaptation and Digital Transformation of MSMEs - Budi Safatul Anam; Hendri Mauliansyah (SUMBER INFORMASI MANAJEMEN BISNIS DAN AKUNTANSI, 2024)
This study examines how micro, small, and medium enterprises (MSMEs) navigate modern retail competition through adaptation strategies and digital transformation. Drawing on a qualitative design complemented with survey-based validation, the research explores the challenges and opportunities faced by MSMEs in adopting technological solutions to enhance competitiveness. Semi-structured interviews with MSME owners, alongside survey data, were analyzed using thematic analysis and descriptive statistics. The findings reveal three critical dimensions: first, the adoption of innovative strategies such as omnichannel integration, product diversification, and customer engagement through digital platforms; second, the role of digital transformation, where e-commerce adoption, digital payment systems, and data-driven decision-making significantly improve operational efficiency and market reach; and third, persistent barriers including financial constraints, limited digital literacy, and cultural resistance that undermine successful adoption. Case studies, such as Warung Pintar in Indonesia and artisan cooperatives in Kenya, illustrate how digital tools can improve resilience, expand customer bases, and foster collaboration among MSMEs. The study highlights that enterprises capable of aligning digital tools with consumer preferences and building collaborative ecosystems are more likely to achieve sustainable competitiveness. The research contributes to the literature by integrating adaptation and digital transformation into a unified framework, while offering managerial and policy implications for promoting inclusive digitalization and strengthening MSME resilience in an increasingly competitive retail landscape.